A Methodological Exploration of Reason and Mysticism in Defining Divine Revelation: The Perspectives of Ibn Sīnā and Al-Ghazālī: Eksplorasi Metodologis tentang Akal dan Mistisisme dalam Mendefinisikan Wahyu Ilahi: Perspektif Ibn Sīnā dan Al-Ghazālī - Erdogan Ibrahim (Senarai: Journal of Islamic Heritage and Civilization, 2025)
This article delves into the contrasting conceptions of divine revelation as articulated by two significant figures in Islamic thought, Ibn Sīnā and Al-Ghazālī, within the framework of metaphysical and epistemological processes. Ibn Sīnā views divine revelation as a metaphysical process situated at the apex of intellect. He posits it as an abstract reflection of divine knowledge conveyed to the prophet's imaginative faculty through the Active Intellect, a process philosophically grounded in the maturation of human intellectual capacity. Conversely, Al-Ghazālī understands divine revelation as a mystical experience, a divine encounter that surpasses the boundaries of human reason. For Al-Ghazālī, divine revelation manifests as an expression of God's speech, occurring solely through divine volition and inherently resistant to full rational comprehension. His Sufi-oriented perspective considers divine revelation integral to spiritual development. Through a comparative analysis of these two thinkers' understandings of divine revelation and metaphysics examining the points of convergence and divergence between Ibn Sīnā's rational approach and Al-Ghazālī's intuitive and inspirational Sufi approach this study offers an in-depth exploration of the evolution of the concept of divine revelation within Islamic theology and philosophy, underscoring the distinct contributions of each thinker to this intellectual tradition.